VSCode for the web. (Pragmatic AI Solutions, 2022)
VSCode for the web Use VSCode directly on the web for editing Git repos Although you can use VSCode locally, using it in the web allows you to avoid having an install and dealing with platform problems. There is no account required and you can directly edit GitHub repositories on the web. In the case of Python, there are a couple of constraints that you must be aware of, like no support to run the terminal and execute a Python program. But syntax and intellisense works great, and we can even make Jupyter Notebooks work with the help of an extension. If you are a beginner and trying out different text editors, or even if you are a seasoned developer, you will find a case to use this feature of VSCode. Learning Objectives In this lesson you will learn: Opening a GitHub repository directly on the web and start editing it Commit and push changes from VSCode on the web to GitHub What are the constraints and limitations of the Python support Use Jupyter Notebooks and find what are some of the problems you may find Useful Resources VSCode for the Web documentation Minimal Python book Free Azure Certification for Students Develop web applications with Visual Studio Code.